Pemberdayaan Kelompok Rentan Difabel Melalui Kemitraan Multipihak - Reiki Nauli Harahap ,Arnola Septa Maheswara (Jurnal Masyarakat dan Desa, 2021)
Underdevevechment, poverty and vulnerability become factors inhibiting disability from fulfilling their well-being. Third-party intervention is needed to accelerate the provision of a decent life for people with disabilities.Goverment, businesses, and community groups are faced with different limitations. Synergy becomes the main issue so that the empowerment of vulnerable groups through programs that carried out by multi-parties can run effectively. This research was conducted in Kabupaten Cilacap with qualitative methods and descriptive analysis approaches. This research is guided by convergence theory so that the author can analyze and sharpen the issues that discussed in this paper, so that information is obtained that in an activity multi-stakeholders partnership requires several catalysts as trigger factors and continued with mutual agreement and collective action so that the intended thing can be achieved. Physiotherapy massage training program is an example of best practice in the multi-party partnership agenda to implement the empowerment program of vulnerable groups with disabilities. The creation of welfare for difabel must involve many parties, Pertuni (CSO) stand-in as the main pillars driving change and empowerment, PT Holcim Indonesia Tbk Cilacap Plant (Private sector) as a supporting actor and the Cilacap Regency Government (state) as an actor who exercises control through the formulation of social policies. There are six catalysts that trigger disability empowerment by the three parties including internal stimulus, change angent, innovation, technology, policy and mass media.